A dedutibilidade no contexto do Imposto de Renda Pessoa Jurídica - Charnet, Ana Carolina Scopin (2008)
The Income Tax is ruled by complex and sparse rules, indeed one of the most important tributes in Brazil, reaches both natural persons and legal entities. On account of this amplitude, as a rule, the discussions concerning this tribute raise the interest of studious people and contributors as well, who are always interested in verifying whether the demand to which they are being subject is in accordance to the rules of the system, and, on the other hand, whether there is basis to eventual contestations. Among such discussions the relevant one is related to the definition of income , in other words, the one that aims at specifying limits to the meaning of income for taxation purposes. Therefore, it is necessary to investigate the meaning and understanding of the word income , what is viable from the analysis of facts that form this concept, the increases versus the decreases, the entries versus the expenditures. Under a practical perspective we notice a special complexity in the rules applied to the Income Tax concerning legal entities, due to the fact that in this field, individual concepts of accounting mix, making it more difficult or, at least, making the activity of the Legal Professionals more complex. Being aware of these features our objective in this present work is to broach the materiality of the Income Tax, regarding legal entities, aiming at formulating our concept of income, analyzing the system under the expenditures point of view. Thenceforth comes the importance that reveals itself, for the present study, of the definition of the concept of necessary expenses . It is worth mentioning, in addition, that in order to reach this goal we will start from the verification of constitutional statutes, once, in our view, it is in the Federal Constitution the basic guidelines of the concept of income , balanced by the principles that assure fundamental rights to contributors. Finally, we highlight that our motivation as to the choice of the topic now dealt with comes from the questions that are raised in the practical field, which, sometimes reflect on the jurisprudence positioning, denunciating the need for a deeper reflection on the topic